DOI: 10.11606/t.23.2006.tde-05052006-163253
|View full text |Cite
|
Sign up to set email alerts
|

"Distribuição dos componentes não colágenos da matriz extracelular em tumores odontogênicos"

Abstract: meu sincero agradecimento pelos conhecimentos transmitidos e pela convivência agradável. A todos meus prezados colegas de turma na pós-graduação e valiosos amigos:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…In the present study, ONC expression showed a strongly positive marking in all parameters analyzed in Group II with the exception of the mineralized and osteocyte matrix, confirming the report of the previous study. The weakly positive ONC marking on the mineralized matrix and the osteocytes can be explained by the fact that this protein is more found in cells in the process of calcification when compared to already mineralized tissues [46].…”
Section: International Journal Of Dental Sciences and Researchmentioning
confidence: 99%
“…In the present study, ONC expression showed a strongly positive marking in all parameters analyzed in Group II with the exception of the mineralized and osteocyte matrix, confirming the report of the previous study. The weakly positive ONC marking on the mineralized matrix and the osteocytes can be explained by the fact that this protein is more found in cells in the process of calcification when compared to already mineralized tissues [46].…”
Section: International Journal Of Dental Sciences and Researchmentioning
confidence: 99%